Postural control among elderly women with and without osteoporosis: is there a difference? - Burke, Thomaz Nogueira; França, Fabio Jorge Renovato; Meneses, Sarah Rúbia Ferreira de; Cardoso, Viviam Inhasz; Pereira, Rosa Maria Rodrigues; Danilevicius, Camille Figueredo; Marques, Amélia Pasqual (São Paulo Medical Journal, 2010)
CONTEXT AND OBJECTIVE: Little is known about postural control among elderly individuals with osteoporosis and its relationship with falls. It has been suggested that elderly women with kyphosis and osteoporosis are at greater risk of falling. The aim of this study was to evaluate posture and postural control among elderly women with and without osteoporosis. DESIGN AND SETTING: Cross-sectional study conducted at the Physical Therapy and Electromyography Laboratory, School of Medicine, Universidade de São Paulo (USP). METHODS: Sixty-six elderly women were selected from the bone metabolism disorders clinic, Division of Rheumatology, USP, and were divided into two groups: osteoporosis and controls, according to their bone mineral density (BMD). Postural control was assessed using the Limits of Stability (LOS) test and the Modified Clinical Test of Sensory Interaction and Balance (CTSIBm) and posture, using photometry. RESULTS: The elderly women with osteoporosis swayed at higher velocity on a stable surface with opened eyes (0.30 versus 0.20 degrees/second; P = 0.038). In both groups, the center of pressure (COP) was at 30% in the LOS, but with different placements: 156° in the osteoporosis group and 178° in the controls (P = 0.045). Osteoporosis patients fell more than controls did (1.0 versus 0.0; P = 0.036). CONCLUSIONS: The postural control in elderly women with osteoporosis differed from that of the controls, with higher sway velocity and maximum displacement of COP. Despite postural abnormalities such as hyperkyphosis and forward head, the COP position was posteriorized.